2020
DOI: 10.3390/nu12030592
|View full text |Cite
|
Sign up to set email alerts
|

Is Abdominal Fat Distribution Associated with Chronotype in Adults Independently of Lifestyle Factors?

Abstract: Both abdominal obesity and its visceral component are independently associated with cardiometabolic diseases. Among the non-modifiable and modifiable determinants, lifestyle plays a central role, while chronotype is an emerging factor. Evening type (E-Type), more active and efficient in the last part of the day, has been associated with a health-impairing style, resulting in a higher risk of obesity and cardiometabolic diseases than morning type (M-Type). However, no study has examined the contribution of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
8
24
0
1
Order By: Relevance
“…Indeed, we found that subjects with evening chronotype had lower adherence to the MD compared to the two other categories. Our findings were in agreement with a previous cross-sectional study performed in 416 middle-aged adults aiming at investigating the contribution of chronotype to abdominal fat distribution and collaterally reporting a higher adherence to the MD in subjects with morning chronotype compared to those with intermediate and/or evening chronotype [29]. However, in this study the authors investigated the association between the adherence to the MD in terms of PREDIMED score and chronotype categories.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we found that subjects with evening chronotype had lower adherence to the MD compared to the two other categories. Our findings were in agreement with a previous cross-sectional study performed in 416 middle-aged adults aiming at investigating the contribution of chronotype to abdominal fat distribution and collaterally reporting a higher adherence to the MD in subjects with morning chronotype compared to those with intermediate and/or evening chronotype [29]. However, in this study the authors investigated the association between the adherence to the MD in terms of PREDIMED score and chronotype categories.…”
Section: Discussionsupporting
confidence: 92%
“…Central obesity independent of BMI is the key factor in the development of MetS. Besides hereditable determinants, modifying lifestyle factors such as dietary habits, physical activity, and to a certain extent, smoking status, remain the major driving force [ 24 ]). Overall, elderly women in HCHS followed a favorable lifestyle compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the traditional Mediterranean diet was assessed using a validated 14-item questionnaire [ 31 ]. The guidelines set out by the Prevención con Dieta Mediterránea (PREDIMED) study group ( www.predimed.es ) with some adaptation already employed in previous studies were used to obtain the Mediterranean score (MED score) [ 32 , 33 ]. One point was attributed for each of the following: (1) olive oil as the main cooking fat; (2) olive oil ≥ 4 tablespoons/day; (3) vegetables > 2 servings/day (or ≥ 1 portion raw or salad) [ 31 ]; (4) fruit ≥ 3 servings/day; (5) red or processed meat < 1 serving/day; (6) butter or cream or margarine < 1/day; (7) sugar-sweetened beverages < 1/day; (8) wine ≥ 3 glasses/week; (9) legumes ≥ 3 servings/week; (10) fish/seafood ≥ 3 servings/week; (11) commercial sweets and confectionery < 3/week; (12) nuts ≥ 1/week; (13) white more than red meats (yes); and (14) use of sofrito ≥ 2/week.…”
Section: Methodsmentioning
confidence: 99%